2018
DOI: 10.1007/s11239-018-1647-9
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab for acute treatment and prophylaxis of a patient with multiple relapses of acquired thrombotic thrombocytopenic purpura

Abstract: Acquired thrombotic thrombocytopenic purpura (TTP) is an autoimmune disorder resulting in potentially life-threating systemic thrombotic microangiopathy due to production of antibodies directed against the von Willebrand factor-cleaving protease ADAMTS13. Typically managed with plasma exchange, glucocorticoids, and the first-generation anti-CD20 monoclonal antibody rituximab, patients with multiple relapses or refractory disease present unique management challenges. We describe a case of a young woman with mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…As stated above, we suggest caplacizumab as a first line agent in all severe TTP patients, especially with a high and prolonged risk of thromboembolic events and sudden death 17,103 . In case of failure of rituximab, ofatumumab might be an option 109 . It has also been suggested that in patients unresponsive to treatment, centrifugation devices might be preferred over plasma filters (lower shear stress rates).…”
Section: Grade: Expert Opinion Agreement: Strongmentioning
confidence: 99%
“…As stated above, we suggest caplacizumab as a first line agent in all severe TTP patients, especially with a high and prolonged risk of thromboembolic events and sudden death 17,103 . In case of failure of rituximab, ofatumumab might be an option 109 . It has also been suggested that in patients unresponsive to treatment, centrifugation devices might be preferred over plasma filters (lower shear stress rates).…”
Section: Grade: Expert Opinion Agreement: Strongmentioning
confidence: 99%
“…The former is also currently licensed for the use in relapsing multiple sclerosis 13,15 . Case reports of the successful use of both mAbs leading to disease remission have been described by ours and other centres in patients with iTTP who have not tolerated rituximab, although some cross‐reactivity of side‐effects were described in one case 16–19 …”
Section: Introductionmentioning
confidence: 73%
“…13,15 Case reports of the successful use of both mAbs leading to disease remission have been described by ours and other centres in patients with iTTP who have not tolerated rituximab, although some cross-reactivity of side-effects were described in one case. [16][17][18][19] As a result of this, we aimed to evaluate the use of ofatumumab and obinutuzumab for iTTP in the UK to assess their clinical efficacy and safety profile in those who have not tolerated rituximab previously or shown poor responses.…”
Section: Introductionmentioning
confidence: 99%
“… 48 Patients who fail or become intolerant to rituximab may benefit from treatment with other anti-CD20 antibodies (eg obinutuzumab 49 or ofatumumab). 50 …”
Section: Adamts13 Supplementation: Therapeutic Plasma Exchangesmentioning
confidence: 99%